A nonlinear dynamic model of fiber-reinforced composite thin plate with temperature dependence in thermal environment. (1st April 2019) - Li, Hui; Wu, Huaishuai; Zhang, Tinan; Wen, Bangchun; Guan, Zhongwei
Abstract: In this paper, the material nonlinearity induced by the high temperature is introduced in the modeling of fiber-reinforced composite thin plate structure, and a nonlinear dynamic model in thermal environment is established using Hamilton's principle in conjunction with the classical laminated plate theory, complex modulus method and strain energy method. The nonlinear relationships between the elastic moduli, Poisson's ratios and loss factors and temperature change are expressed by the polynomial method. Then, the dynamic equations in the high temperature environment are derived to solve the inherent characteristics, dynamic responses and damping parameters with considering temperature dependent property. Also, the identification principle of concerned fitting coefficients in the theoretical model is illustrated. As an example to demonstrate the feasibility of the developed model, the experimental test of a TC500 carbon/epoxy composite thin plate is implemented. The results of the developed model and experimental test show a good consistency, and both indicate that the high temperature has complicated influence on its dynamic characteristics, especially on damping property.